Oceanographic Data of the 55th Japanese Antarctic Research Expedition from December 2013 to March 2014 - YOSHIYAMA, Takeshi (国立極地研究所, 2016)
Fig. 1 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0012.xlsx Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0013.xlsx Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0014.docx Table 3 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0015.xlsx Table 4 | http://polaris.nipr.ac.jp/~parc/pub/v027/nipr_parc_200_0016.docx departmental bulletin paper